Is the university an authoritarian institution? A theoretical exploration with Lacan, Fromm, and Rancière - Ronge, Bastian (Frontiers in Research Metrics and Analytics, 2025)
This article examines the ambivalent role of the contemporary university in the face of rising authoritarianism. While universities are commonly perceived as bastions of humanism, committed to ideals such as freedom, critical inquiry, and Bildung, this optimistic view may obscure the fact that authoritarian dynamics can persist within the institution itself. Rather than labeling the university as an inherently authoritarian institution, the article argues that it constitutes a social field in which authoritarian tendencies may emerge and take effect—often in subtle and structurally embedded forms. The first part of the article reconstructs Jacques Lacan's psychoanalytic account of the university's authoritative structure and its transformation after 1968, focusing on how authority functions discursively within academic contexts. The second part draws on Erich Fromm's theory of the authoritarian character and combines his perspective with Lacan's framework to propose a heuristic model for identifying and analyzing authoritarian dynamics within present-day academic life. In the third part, the article turns to Jacques Rancière's concept of the ignorant schoolmaster as a means of outlining an anti-authoritarian pedagogy. Rancière's approach is presented as a practical and conceptual tool to carve out spaces of resistance and autonomy within the university. Finally, the article reflects on the limitations of its approach and suggests directions for future research.